'Easy listening': Altered Auditory Feedback and dysfluent speech. Issue 1 (1st April 2019) - Stuart, Maria
This article is part of the emergent field of Dysfluency Studies (Eagle 2013 and 2014), an interdisciplinary approach drawing on literary/cultural analysis, clinical practice, neurological research and disability studies to challenge concepts of 'normative' speech and the pathologizing vocabulary that sustains them. While recognizing the widespread presence and function of the 'metaphoric stammer' in cultural practice, it places the corporeal, embodied experience of stammering at the centre of the work. Drawing on this reinvestment in the embodied speaker, the article explores the auditory aspects of dysfluency through a focus on three such 'speakers': George VI (as represented in the film The King's Speech [Hooper, 2010]), composer Alvin Lucier (in his sound art piece I am Sitting in a Room) and vocal artist Victoria Hanna (Voicing Space, Sensing Speech). The King's Speech provides the foundational basis for my focus on auditory 'feedback' (in its therapeutic and neurological forms), a focus that is then 'amplified' through the creative practice of Lucier and Hanna. Implicit in Tom Hooper's film is the power of dysfluency to disrupt dominant narratives of normal speech, a generative power that finds fullest (yet individuated) expression in the embodied performances of Lucier and Hanna.